Fatal case of amoebic liver abscess in a child - Khuen, Foong Ng; Kah, Kee Tan; Romano, Ngui; Yvonne Ai, Lian Lim; Amirah, Amir; Yamuna, Rajoo; Hamimah, Hassan; Rohela, Mahmud (Elsevier B.V., 2015)
We reported a case of amoebic liver abscess (ALA) in a 6-year-old Malaysian boy who presented with fever, lethargy, diarrhoea and right hypochondriac pain. On admission he was diagnosed with perforated acute appendicitis and a laparotomy was done. After surgery he developed acute respiratory distress. Ultrasonography, chest X-Ray and CT scan revealed two ALAs in the posterior segment of right lobe of liver, pleural effusion and collapsed consolidation of lungs bilaterally. Percutaneous liver abscesses drainage was done and intravenous Metronidazole was started. PCR carried out on the pus from the abscess was positive for Entamoeba histolytica. Patient however succumbed to the infection one week after admission.